Exposing hate : prejudice, hatred, and violence in action - Miller, Michael, 1958- (Twenty-First Century Books, 2019)
Profiles hate groups in America from the early religious intolerance in the seventeenth century through the modern spike after the election of Donald Trump. Discusses the motives behind various types of hate groups, be it anti-Semitism, anti-immigration, or male supremacy, and what's being done to counter them.